Economic policy and planning in India Professor Baljit Singh commemoration volume - Singh, A. K. (ed.); Papola, T. S. (ed.); Singh, A. K. (ed.) (New Delhi Sterling Publishers, 1984)
Investment criteria and cholic e of techniques of production